Digital Signal Processing, A Computer Based Approach. 2nd Edition : Sanjit K. Mitra, Ph.D., Mc.Graw Hill 2001. ISBN 0-07-252261-5 - Jaquenod, Guillermo A. (2003)
Designed for a one-year course on DSP, the book Digital Signal Processing, A Computer Based Approach aims to give seniors or first-year graduate students strong foundations of the analysis and design of discrete-time systems for digital signal processing. Anyway, is also suitable for self-study by practicing engineers or scientists. Numerous practical examples using real life signal processing problems are given, emphasizing the mastery of concepts and tools rather than rigor of mathematics.